2018
DOI: 10.1007/s00382-018-4412-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CORDEX simulations over South America: added value on seasonal climatology and resolution considerations

Abstract: A new set of CORDEX simulations over South America, together with their coarserresolution driving Global Climate Models (GCMs) are used to investigate added value of Regional Climate Models (RCMs) in reproducing mean climate conditions over the continent. There are two types of simulations with different lateral boundary conditions: five hindcast simulations use re-analysis as boundary conditions, and five other historical simulations use GCMs outputs. Multi-model ensemble means and individual simulations are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 61 publications
2
35
0
1
Order By: Relevance
“…(). The two models have been used extensively over South America in different international projects such as CLARIS, CLARIS‐LPB and CORDEX (Menéndez et al ., , , ; Carril et al ., ; Ruscica et al ., , , ; Sánchez et al ., ; Falco et al ., ; Spennemann et al ., ; Zaninelli et al ., ). The spatial domain includes the South American continent and adjacent oceans at approximately 50 km resolution and the models were driven every 6 hr with boundary conditions from ERA‐Interim reanalysis (Dee et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…(). The two models have been used extensively over South America in different international projects such as CLARIS, CLARIS‐LPB and CORDEX (Menéndez et al ., , , ; Carril et al ., ; Ruscica et al ., , , ; Sánchez et al ., ; Falco et al ., ; Spennemann et al ., ; Zaninelli et al ., ). The spatial domain includes the South American continent and adjacent oceans at approximately 50 km resolution and the models were driven every 6 hr with boundary conditions from ERA‐Interim reanalysis (Dee et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…ERA5 has a finer spatial and temporal resolution and a better global balance of precipitation and evaporation than ERA‐Interim, among other improvements (Copernicus Climate Change Service (C3S), 2017). The version of RCA4 considered in this study is currently used within CORDEX (http://www.cordex.org) and has been used over South America in previous studies (Spennemann et al ., 2018; Falco et al ., 2019; Giles et al ., 2019; Menéndez et al ., 2019; Zaninelli et al ., 2019), to which the reader can refer for more information about the model's configuration and performance. The spatial resolution is 25 and 50 km for ERA5 and RCA4, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The origin of these biases lies, at least partly, in unresolved topographical forcing which remains too smoothed over the complex terrain of the Andes, limiting the simulation of regional processes such as the interactions between local circulation and orography, a key factor in climate modulation at meso-scale levels. However, even considering these systematic biases, recent studies have confirmed that CORDEX-type RCMs (e.g., with a spatial resolution of 20-50 km) have the potential to add value in the representation of extreme precipitation and mean surface temperature over the Andes (Falco et al, 2018(Falco et al, , 2019Bozkurt et al, 2019).…”
Section: Regional Climate Downscalingmentioning
confidence: 99%